Advancements in industrial supply chain through lean implementation - a review - Ahmed Zainul, Abideen; Fazeeda, Mohamad (Inderscience Enterprises Ltd., 2020)
Previously, lean management was adopted to reduce wastes in the core production processes. But now, it has started addressing issues in other operational scenarios. Its scope can be expatiated several notches higher, even after attaining 'Industry 4.0'. Customers want expeditious and cheaper finished products. Major companies are now seeking competent methods to reduce wastes in their supply chain. Engagement of lean tools and concepts in the supply chain has proven to have diminished scrap and cycle time over the past few years. Many studies have been carried out to design the supply chain from the lean's perspective. The objective of this study is to conduct a systematic review of selected articles on the 'lean supply chain'. Research articles between the year 2000 and 2017 were collected strictly adhering to the selected keywords and exclusion criteria. Another objective was to plot down the developments in lean supply chain.